Ecofriendly/Rapid Synthesis of Silver Nanoparticles Using Extract of Waste Parts of Artichoke (Cynara scolymus L.) and Evaluation of their Cytotoxic and Antibacterial Activities. (14th September 2021) - Baran, Ayşe; Baran, Mehmet Fırat; Keskin, Cumali; Kandemir, Sevgi Irtegun; Valiyeva, Mahbuba; Mehraliyeva, Sevil; Khalilov, Rovshan; Eftekhari, Aziz
Abstract : Recycling wastes and providing their use in useful fields attract attention every day. In our study, with the extract prepared from the parts of the Cynara scolymus L. (artichoke) plant that is not suitable for human consumption, silver nanoparticles were easily synthesized in an ec-friendly, energy-free way. Characterization of the obtained nanoparticles was done with a UV-visible spectrophotometer (UV-Vis.), fourier transform infrared spectroscopy (FTIR), X-ray diffraction diffractometer (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), and zeta potential analysis data. In these data, it was determined that AgNPs have a maximum absorbance at 458.8 nm wavelength, a crystal nanosize of 28.78 nm, and a spherical appearance. The zeta potential of (-) 16.9 mV indicates that silver nanoparticles exhibit a stable structure. Particles show antimicrobial effects on pathogenic species at concentrations of 0.03-0.25  μ g/ml, and it was determined by using the minimum inhibition concentration (MIC) microdilution method. By examining their cytotoxic effects on U118, CaCo-2, and Skov-3 cancer cell lines and healthy HDF cell lines by the MTT method, concentrations of inhibitive effects on survival were determined.